(3GdCUjdjs - (3GdYdhj, CHh LYaQ, GHf GdWbWbj, eMeO Hf Ydj Hf eMeO GHf WHGWHG, J (B709 (3g`s ((3GdeTgO GdQVhjs)
(3ChdgG (B:s
... (3hLg SHH GdbWY Gf jSJHjf aQGL GdaQhY hjPcQ GJUGd aQY dG fSJTgO Hg ddTLQGJ (B..(3GdGfJbGd hdG NWhW TGFjf Pdc agh efbWY hZfcGQ GdCHhjf HbWjYI CjVG hGYJQGage HYO GdGfcGQ (B...s
(3BNQgG (B:s
.. (3ace ef QMe ebWhYI hUdJ fSHgG KGd ef bQjI cPG hbGd Ydjg GdSdGe ef YQa fSHg bOQg hef de jYQa fSHg dG bOQ dg hbGd GHf YHGS JYdehG (B...s
(3JHUQI GdYfhGf (B:s
(3HMQ GdCfSGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdGYdGe (B6\283s
(3GdPQjYI (B21 - 30 ( 3877 )s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs